2002
DOI: 10.1177/172460080201700302
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intraoperative Manipulation of the Prostate on Total and Free Prostate-Specific Antigen

Abstract: Objectives: It is well documented that mechanical manipulation of the prostate can elevate total PSA (t-PSA) levels in serum. However, less is known about its effects on free PSA (f-PSA) and the free-to-total PSA ratio (f/t-PSA). We therefore examined the impact of prostate manipulation on t-PSA and f-PSA during surgical procedures involving the prostate. Methods: Intraoperative blood samples for t-PSA and f-PSA measurement (Hybritech) were collected every 15 min during 14 radical retropubic prostatectomies (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…The present study demonstrated that four (P = 0.00) and six (P = 0.00) weeks of prostatic massage improve PSA in patients with PC, and this is inconsistent with other studies examining the individual effects of prostatic massage after ADT, chronic prostatitis, and radiation therapy (5,26). Likewise, it has been reported that free PSA is the most increased form after prostatic manipulation (5,27). In addition, the current study demonstrated that four (P = 0.00) and eight (P = 0.00) weeks of resistance training reduce PSA.…”
Section: Discussioncontrasting
confidence: 54%
“…The present study demonstrated that four (P = 0.00) and six (P = 0.00) weeks of prostatic massage improve PSA in patients with PC, and this is inconsistent with other studies examining the individual effects of prostatic massage after ADT, chronic prostatitis, and radiation therapy (5,26). Likewise, it has been reported that free PSA is the most increased form after prostatic manipulation (5,27). In addition, the current study demonstrated that four (P = 0.00) and eight (P = 0.00) weeks of resistance training reduce PSA.…”
Section: Discussioncontrasting
confidence: 54%
“…If prior collection is not possible, then it is prudent to delay several days after DRE before drawing blood for PSA, although in most men DRE does not cause a clinically relevant change in circulating PSA concentration (166 ). Following prostate biopsy or surgery, the recommended delay is several weeks to permit sufficient time for the PSA bound as a stable complex to ␣-1-antichymotrypsin to be eliminated from the blood circulation, although the kidneys rapidly clear from the blood any fPSA that was liberated from the prostate by the procedure (208,209 To eliminate in vitro artifacts, blood should be centrifuged within 3 h of collection to isolate the serum or plasma (210 ). Serum and plasma may be kept at refrigerated temperatures for up to 24 h without loss of PSA.…”
Section: Preanalytical Specimen Processing and Storagementioning
confidence: 99%
“…f-PSA is more sensitive to manipulation and is also cleared from serum faster than t-PSA. Studies evaluating biological clearance rates of f-PSA after surgical removal of the prostate gland suggest a shorter half-life of 22 h (13,14). Studies evaluating biological clearance rates of f-PSA after surgical removal of the prostate gland suggest a shorter half-life of 22 h (13,14).…”
Section: Discussionmentioning
confidence: 99%